HRD Perspectives on Developmental Relationships Connecting and Relating at Work - Ghosh, Rajashi; Hutchins, Holly M. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Developmental relationships constitute interdependent, generative connections that promote growth and learning among individuals. While studies reporting the impact of developmental relationships on learning, performance, and career development leaves no doubt about its relevance to the human resource development (HRD) field, we lack an in-depth understanding of how developmental relationships apply to the myriad of topics relevant to contemporary HRD research and practice such as social justice, diversity and equity, leadership development, career transitions, knowledge sharing, organization development, employee engagement, organizational learning culture, globalization, national HRD, and technology at work. This book presents a comprehensive collection of evidence-based studies and conceptual articles that explore how developmental relationships that are cultivated within and outside of the workplace apply to those clusters of topics in HRD. Organized around six themes, the chapters examine topics such as knowledge management, critical perspectives on gender, diversity, and equity, building a learning organization, talent development, and emotional closeness in the context of virtual workplaces. In doing so, the book highlight how research on developmental relationships can be the underlying thread connecting the otherwise disconnected varied topical foci of HRD research and practice, thus broadening our understanding of the relevance of developmental relationships within the HRD field. This volume advances HRD scholarship and will appeal to researchers interested in exploring the nature and benefits of developmental relationships including mentoring and coaching. Rajashi Ghosh is Associate Professor of Human Resource Development and Chair of the Policy, Organization, and Leadership department in the School of Education at Drexel University, USA. Her research aims to explore how different developmental initiatives (e.g., mentoring, coaching, leadership development) can facilitate workplace learning and development through building inclusive relational spaces and countering the prevalence of workplace incivility. Holly M. Hutchins is Vice Provost of Faculty Success and Professor of Counseling and Higher Education at the University of North Texas, USA. Her research focuses on identifying how inclusive learning and development interventions can be designed and evaluated to support successful application to the work environment.
Chapter 1 -- Together is better: Situating Developmental Relationships within HRD Research and Practice_Chapter 2 -- Using Developmental Relationships to Navigate Career Transitions: Implications for Diverse Populations_Chapter 3 -- Making the connection between Developmental Relationships and Employee Engagement_Chapter 4 -- Coaching the Imposter: Developing Emerging Leaders as they Negotiate Identity and Imposter Concerns_Chapter 5 -- Leaders Fostering Dialogue through Developmental Relationships: An OD Perspective_Chapter 6 -- Inter-generational Developmental Network and the Impact of Technology on Knowledge Creation and Sharing_Chapter 7 -- The Power of Embedded Developmental Relationships:Examining Interdependencies among Informal Learning, Developmental Coaching Relationships, and Organizational Culture_Chapter 8 -- Mentoring Diverse Leaders: The Necessity of Identity Work_Chapter 9 -- Using feminist mentoring to deconstruct privilege and power in developmental relationships: A narrative inquiry_Chapter 10 -- Employee Resource Groups: Enabling Developmental Relationships to Support Socially Just and Morally Inclusive Organizations_Chapter 11 -- Can You Hear Me Now?" Technical and Human Factors in Virtual Developmental Relationships_Chapter 12 -- Using Developmental Relationships to foster Trust in Effective Virtual Teams:Lessons in Emergency Preparedness from the COVID-19 Pandemic_Chapter 13 -- Blurring of Boundaries between Work and Home: The Role of Developmental Relationships in the Future of Work_Chapter 14 -- Successful Expatriation and Repatriation for both Employers and Assignees: A Developmental Network Perspectives_Chapter 15 -- Cross-Cultural Styles of Relating and Connecting in Developmental Relationships_Chapter 16 -- How Developmental Relationships Can Be Used by Organizations and Governments as Tools for National HRD Initiatives: India and Spain_Chapter 17 -- Assessing the Impact of Developmental Relationships in a Humanitarian Context_Chapter 18 -- Needs Assessment in Assessing, Building, and Supporting Developmental Relationships in Organizations_Chapter 19 -- Seeking support from multiple Developers: Assessing optimal structure, content, antecedents, and outcomes of Developmental Networks_Chapter 20 -- Connecting and Relating Through Developmental Relationships.
Keywords: Personnel management; Management; Diversity in the workplace; Industrial organization; Human Resource Development; Management; Diversity Management and Women in Business; Human Resource Management; Organization